Conocimiento en gestión empresarial y gestión tributaria en estudiantes de ciencias de la salud de la Universidad Nacional de la Amazonía Peruana año 2024 - Castro Saldaña, Manuel Alejandro (2025)
The level of knowledge in business and tax management among health professionals and students can lead to significant consequences, such as financial and operational problems, tax non-compliance, loss of financing opportunities, impact on the quality of care, staff demotivation and limitations in the business development of this important economic sector, the purpose of the research is to determine the level of knowledge in business management and tax management in health sciences students from the National University of the Peruvian Amazon, 2024, of an observational and descriptive type, from a quantitative approach and a non-experimental design, the results identify that the level of knowledge in business and tax management of health sciences students is generally low, highlighting strengths in areas such as business strategy and issuance of electronic payment vouchers, students have significant deficiencies in project management and the use of business information systems, in the tax field, the management of tools such as the issuance of electronic vouchers and tax returns is limited, which restricts their ability to apply this knowledge In real situations, students also demonstrate competence in leadership and business strategy, but they require more training in processes and technologies, so an improvement in practical training is recommended to successfully face the challenges of the business market in the health sector.